SEASONAL VARIATION IN SEMEN PRODUCTION PARAMETERS OF GIR BULLS REARED UNDER TROPICAL CLIMATE - DAS, S; SANA, D; GUPTA, T; CHOWDHURY, S; CHAKRABORTI, A; BISWAS, J; SARKAR, S (The Indian Journal of Animal Reproduction, 2017)
The present study revealed that the semen production potential and semen ejaculate attributes of Gir breeding bulls maintained under tropical climatic conditions were influenced by the season. Sperm concentration as well as semen doses frozen and stored per ejaculate were higher (p<0.05) in winter compared to rainy and summer season. In brief, among all the three seasons, winter contributed maximum towards annual production of frozen semen doses followed by rainy and summer season.